Psychological predictors of advanced cancer patients' preferences for return of results from comprehensive tumor genomic profiling. Issue 3 (10th November 2021) - Meiser, Bettina; Butow, Phyllis; Davies, Grace; Napier, Christine E.; Schlub, Timothy E.; Bartley, Nicci; Juraskova, Ilona; Ballinger, Mandy L.; Thomas, David M.; Tucker, Kathy; Goldstein, David; Biesecker, Barbara B.; et al.
Abstract: This study assessed the psychological predictors of preferences for return of comprehensive tumor genomic profiling (CTGP) results in patients with advanced cancers, enrolled in the Molecular Screening and Therapeutics Program. Patients completed a questionnaire prior to undergoing CTGP. Of the 1434 who completed a questionnaire, 96% would like to receive results that can guide treatment for their cancer, and preference for receiving this type of result was associated with lower tolerance of uncertainty. Sixty‐four percent would like to receive results that cannot guide treatment, and lower tolerance of uncertainty, self‐efficacy, and perceived importance were associated with this preference. Fifty‐nine percent would like to receive variants of unknown significance, which was associated with lower tolerance of uncertainty, higher self‐efficacy, and perceived importance. Eighty‐six percent wanted to receive germline results that could inform family risk . This was associated with higher self‐efficacy, perceived importance, and perceived susceptibility. Although most patients wanted to receive all types of results, given the differing patient preferences regarding the return of results depending on the utility of the different types of results, it appears critical to safeguard patient understanding of result utility to achieve informed patient choices. This should be accompanied by appropriate consent processes.